PENGARUH BUDAYA BIROKRASI TERHADAP EFEKTIVITAS KERJA PEGAWAI NEGERI SIPIL (Suatu Studi di Sekretariat Daerah Kabupaten Kepulauan Sula) - Umaternate, ROSITA; Ogotan, Martha; Dengo, Salmin (Sam Ratulangi University, 2015)
ABSTRACT: This study aims to a system or set of a value which has a symbol, value orientations, beliefs,knowledge and experience are internalized into the life of the mind. A set of values is actualized in attitudes,behaviors, and actions undertaken by every member of an organization / bureaucracy. Therefore, thebureaucratic culture will affect the effectiveness of the civil servants. In this regard, this research is intended todetermine / measure the extent of bureaucratic culture influence on the effectiveness of civil servants in theRegional Secretariat Sula Islands.This study uses quantitative methods. Respondents are as many as 35 employees were taken at randomfrom the 119 employees of the Regional Secretariat Sula Islands. Instruments and data collection techniquesused were questionnaires and aided by structured interview (interview quide). The analysis technique used totest the hypothesis is simple regression statistical analysis and simple correlation or koreasi product moment.Results and formulation: (1) variable regression coefficient toward bureaucratic culture of the effectiveness ofemployee is posifive and significant at the 0.01 level of significance or confidence level of 99%. (2) thecorrelation coefficient and the coefficient of determination variables bureaucratic culture of the effectiveness ofemployee is significant at a significance level of 0.01 ata 99% confidence levelBased on the results of that study concluded that the bureaucratic culture have a relationship and apositive and significant impact on the effectiveness of employees working in the Regional Secretariat SulaIslands. Thus the bureaucratic culture is one of the determinant factors / determinants of the level of employeeeffectiveness.Starting from these conclusions are advised let the cultural dimension